NGS-based IG/TR gene rearrangement profiling in acute lymphoblastic leukemia: age dependence of immunogenetic maturation - Kotrová, Michaela; Proske, Constantin; Darzentas, Nikos; Laqua, Anna; Kehden, Britta; Kässens, Jan; Bendig, Sonja; Kohlscheen, Saskia; Szczepanowski, Monika; Wessels, Wiebke; Antic, Željko; Pott, Christiane; et al. (Blood, 2025)
We comprehensively profiled the landscape of immunoglobulin (IG) and T-cell receptor (TR) rearrangements at diagnosis in 1212 patients with acute lymphoblastic leukemia (ALL; 573 children and 639 adults) diagnosed in Germany between 2017 and 2022. Our study revealed a significant age-related decrease in immunogenetic maturation, where IG κ rearrangements in B-ALL and complete TR β/δ rearrangements in T-ALL, hallmarks of maturity, were more frequent in pediatric patients compared to adults (B-ALL: 68.7% vs 39.0%, P < 2.2e-16; T-ALL: 85.7% vs 67.3%, P = 6.7e-03). Compared to adults, children had a higher average number of IG/TR markers per patient (6 vs 4; P = 2.5e-38) and markedly fewer lacked these markers (0.5% compared to 6.7%). IG heavy chain clonal evolution was most pronounced among pro-B-ALL cases (60.9%), with the V-to-DJ mechanism driving pro-B evolution (78.6%), whereas V-replacement dominated other immunophenotypes. Furthermore, expanded accompanying T-cell clones of unknown significance in B-ALL increased with age. This next-generation sequencing-based study offers an unprecedented characterization of IG/TR rearrangement patterns across ALL subtypes and age groups. It highlights the higher immunogenetic maturity in children, which may be explained by the infection-driven abnormal activity of the IG/TR recombination machinery in pediatric ALL.